Quality of life in children with acute lymphoblastic leukemia under chemotherapy: A review - Hadi Hayati; Abbas Kebriaeezadeh; Shekoufeh Nikfar; Mohammad Ali Ehsani; Bahman Khosravi; Mahdi Toroski; Amin Hasanvand; Bereket Molla Tigabu (Tehran University of Medical Sciences, 2018)
Background: Acute lymphoblastic leukemia (ALL) is the most common type of leukemia in children, often prevalent in children between the age of 2 and 6 years. However, it can lead to a loss of many years of life in these patients. Therefore, considering the importance of quality of life (QOL) for patients during treatment or after treatment discontinuation, and the extent of the therapeutic protocols, tools, and methods used to measure the QOL of children, we have undertaken a comprehensive review of the QOL of these patients. Methods: In designing a review of the outcomes, consultation with internal clinical experts was implemented first to identify relevant keywords and outcomes. We reviewed all English-language studies from 2000 to 2015 based on the Web of Science, PubMed, and Scopus databases. Results: 2621 studies were first identified in relevant electronic databases. However, only 10 studies met our inclusion criteria. Most of the selected studies used Health Utilities Index Mark 2 (HUI2) and 3 (HUI3) for assessing children's QOL. Some were interviewed by proxy, such as parents and even doctors and nurses involved in the treatment process. Most of the studies reported improvement of utility from 0.67% to 0.96% that in survivors varied from 0.71% to 0.94%. Conclusion: The results of this study illustrated that the treatment of patients with ALL in recent years has developed dramatically in different countries; and consequently, the QOL of these patients improved both during and after treatment.